2009
DOI: 10.1002/edn.142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of routine education on people newly diagnosed with type 2 diabetes

Abstract: Background: In Ireland, there is limited knowledge about the perceptions or behaviours of people newly diagnosed with diabetes and, due to the lack of a national register, poor knowledge of their demographic profile. Aim: To add to the body of knowledge about diabetes, to obtain perceptions of people newly diagnosed with type 2 diabetes who attend group diabetes education, and to examine their relationships with the adoption of diabetes self-management behaviours. Method: A correlational study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 34 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…None of the included studies scored the maximum quality score of 9 points. Among the 14 reviewed studies, one (Trief et al, ) had a methodological quality score of 8, one (Wattana, Srisuphan, Pothiban, & Upchurch, ) had a score of 6, four (Atak, ; Hawkins, ; Moriyama et al, ; Wu et al, ) had 5, two (Siminerio, Ruppert, Emerson, Solano, & Piatt, ; Wu, Liang, Lee, Yu, & Kao, ) had 2, and the remaining 6 studies (Clarke, ; Johnson et al, ; Karakurt & Kas¸ıkçı, ; Landim, Zanetti, Santos, Andrade, & Teixeira, ; McEwen et al, ; Ve'g, Rosenqvist, & Sarkadi, ) had a quality score of 1 (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…None of the included studies scored the maximum quality score of 9 points. Among the 14 reviewed studies, one (Trief et al, ) had a methodological quality score of 8, one (Wattana, Srisuphan, Pothiban, & Upchurch, ) had a score of 6, four (Atak, ; Hawkins, ; Moriyama et al, ; Wu et al, ) had 5, two (Siminerio, Ruppert, Emerson, Solano, & Piatt, ; Wu, Liang, Lee, Yu, & Kao, ) had 2, and the remaining 6 studies (Clarke, ; Johnson et al, ; Karakurt & Kas¸ıkçı, ; Landim, Zanetti, Santos, Andrade, & Teixeira, ; McEwen et al, ; Ve'g, Rosenqvist, & Sarkadi, ) had a quality score of 1 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of interventions used in improving self‐management skills among people with type 2 diabetes. Diabetes self‐management programmes of reviewed studies had patient education delivered in individual and group sessions (Clarke, ; Karakurt & Kas¸ıkçı, ; Landim et al, ; McEwen et al, ; Siminerio et al, ; Wattana et al, ) on diabetes self‐care (Wu et al, ), pathology, healthy lifestyle habits, medication use and adherence (Johnson et al, ), self‐management behaviour, diet, exercise, complications of weight control, and foot care (Atak, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Clarke’s study (Clarke, 2009), the questionnaire was modified to measure self-reported dietary fat intake behavior. Internal consistency reliability was the only form of psychometrics testing, with an acceptable level.…”
Section: Resultsmentioning
confidence: 99%